A structural tonk. - Fiore, Camillo (Analysis, 2024)
When logicians work with multiple-conclusion systems, they use a metalinguistic comma ',' to aggregate premisses and/or conclusions. In this note, I present an analogy between this comma and Prior's infamous connective tonk. The analogy reveals that these expressions have much in common. I argue that, indeed, the comma can be seen as a structural incarnation of tonk. The upshot is that, whatever story one has to tell about tonk , there are good reasons to tell a similar story about the comma in typical multiple-conclusion systems, and vice versa.